How is climate change adaptation aid allocated? A study of climate justice in Ecuador - Paul Cisneros; Mercy Ilbay-Yupa (Desarrollo y Sociedad, 2023)
This paper analyses the allocation of climate adaptation aid in subnational and local jurisdictions in Ecuador. It examines the influence of physical and socioeconomic vulnerability and local capacity as independent variables of aid allocation. The study introduces projections of physical vulnerability to determine whether inter-generational aspects of climate justice are taken into account and uses geographically weighted regression models to study the spatial distribution of aid allocation. The findings show that physical and socioeconomic vulnerabilities influence adaptation aid allocation. However, projected changes in patterns of precipitation and temperatures are not associated with this variable. Furthermore, the spatial distribution of current climate aid is uneven, leaving clusters of vulnerable jurisdictions unattended. Finally, the study finds no association between local capacity and adaptation aid allocation. Findings suggest that the allocation of adaptation aid may not contribute to achieving adaptation scenarios where justice for current and future generations is central to decision-making.